PENERAPAN PENILAIAN KESEHATAN KOPERASI PADA KOPERASI SIMPAN PINJAM KOZERO KOTA SUNGAI PENUH - Zachari Abdallah; Maryanto Maryanto (LP2M Universitas Bina Bangsa, 2024)
This study is intended to analyze the health level of cooperatives in the Kozero Savings and Loans Cooperative in 2023 in terms of aspects of governance, risk profile, financial performance, and capital based on the Deputy Technical Guidelines for Cooperative Affairs Number 15 of 2021 concerning Guidelines for Cooperative Health Examination Working Papers. This type of research is descriptive research with a quantitative approach. The data used in this study are 2023 financial statements, 2023 loan collectibility data, and answers to questionnaires. Sungai Full City has many savings and loan cooperatives, one of which is the Kozero Save and Loan Cooperative which is located in Pelayang Raya village, Sungai Bungkal District. Know that in the capital aspect, a score of 11.3 was obtained, the quality aspect of productive assets was 9.25, the management aspect was 15, the efficiency aspect was 5, the liquidity aspect was 7.5, the independence and growth aspect was 10, and the cooperative identity aspect was 5.25 in the identity aspect of PPP Kozero did not carry out a member promotion ratio so that the section was declared empty. After getting the number of scores per aspect, a total score of 63.3 was obtained, this number shows that the cooperative health quality predicate is quite healthy